Rekonstruksi Paradigma Guru TK Mengintegrasikan Logika Coding dan Deep Learning dalam Pembelajaran Berbasis Bermain (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital era demands a fundamental transformation in the role of early childhood educators, shifting from passive technology consumers to active architects of digital literacy. However, the dominance of technocentric views often acts as a substantial psychological and pedagogical barrier for teachers in regional areas. This collaborative community service project aims to reconstruct the paradigm of 50 kindergarten teachers in Bulukumba Regency by integrating